Analisis Perubahan Nama Gereja Dayak Evangelis Menjadi Gereja Kalimantan Evangelis: Studi Histografi - Saputra, Hadi (Institut Agama Kristen Negeri Palangka Raya, 2023)
So far, the history of the Kalimantan Evangelical Church (GKE) has always been associated with the efforts of the Dayak Evangelical Church (GDE) to become GKE, only looking at it from an ecumenical perspective, despite the fact that there is something very important, namely the removal of the Colonial roots behind the embedded Dayak word. In the struggle for independence that existed at that time, the word